2023
DOI: 10.3847/1538-3881/aca80b
|View full text |Cite
|
Sign up to set email alerts
|

The Kinematics and Excitation of Infrared Water Vapor Emission from Planet-forming Disks: Results from Spectrally Resolved Surveys and Guidelines for JWST Spectra

Abstract: This work presents ground-based spectrally resolved water emission at R = 30,000–100,000 over infrared wavelengths covered by the JWST (2.9–12.8 μm). Two new surveys with iSHELL and the VISIR are combined with previous spectra from the CRIRES to cover parts of multiple rovibrational and rotational bands observable within telluric transmission bands, for a total of ≈160 spectra and 85 disks (30 of which are JWST targets in Cycle 1). The general expectation of a range of regions and excitation conditions traced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 128 publications
9
24
0
Order By: Relevance
“…Compared to previous Spitzer spectra, most of these lines are now deblended in the MIRI spectrum, with some blending still visible at the shortest wavelengths. In Figure 3, we show two slab models for water using properties previously found from fits to high-resolution ground-based spectra of other T Tauri disks (Banzatti et al 2023): T ∼ 1000 K for the rovibrational lines below 6.6 μm and T ∼ 600 K for the rotational lines at 13-16 μm, and a similar column density of ≈10 17 -10 18 cm −2 .…”
Section: Gas Featuresmentioning
confidence: 97%
“…Compared to previous Spitzer spectra, most of these lines are now deblended in the MIRI spectrum, with some blending still visible at the shortest wavelengths. In Figure 3, we show two slab models for water using properties previously found from fits to high-resolution ground-based spectra of other T Tauri disks (Banzatti et al 2023): T ∼ 1000 K for the rovibrational lines below 6.6 μm and T ∼ 600 K for the rotational lines at 13-16 μm, and a similar column density of ≈10 17 -10 18 cm −2 .…”
Section: Gas Featuresmentioning
confidence: 97%
“…35,78–81 However, even methanol turns out to be a species difficult to detect in protoplanetary disks, 82 maybe because of the large dust opacity that absorbs much of its emission 83 or the relatively low temperature. 84 Fortunately, the new observations of JWST are already giving plenty of information on the inner regions of the disk, 85–87 an appetizer of which is also reported in this volume ( e.g. , van Dishoeck et al and Kamp et al ).…”
Section: Observations Of Icoms and Ices In Solar-type Star Forming Re...mentioning
confidence: 78%
“…The most prominent characteristic of this spectrum is the forest of water lines, from the hot bending rovibrational band at ∼6.6 μm to the cooler pure rotational lines at longer wavelengths (see, e.g., Figure 1 in Banzatti et al 2023b). In relation to water emission, Sz 114 is very different from other mid-to-late M-star disks observed with Spitzer/IRS (Pascucci et al 2013) and the similarly late M5 object recently observed with MIRI-MRS (J160532; Tabone et al 2023) in which water emission was either very weak or absent.…”
Section: The Water-rich Mid-infrared Spectrum Of Sz 114mentioning
confidence: 99%
“…Most of the volatile oxygen and carbon are carried by H 2 O and CO, while most nitrogen is likely in the undetected form of gas-phase N 2 (e.g., Pontoppidan et al 2014, and references therein). For the brightest disks, high-resolution (R ∼ 25,000-95,000) ground-based telescopes targeted few accessible transitions and spectroscopically confirmed that infrared molecular emission mostly traces gas within a few au from the star (e.g., Pontoppidan et al 2010;Mandell et al 2012;Najita et al 2018;Salyk et al 2019;Banzatti et al 2023b). This is the gas inside the water-ice line (hereafter the snowline) that is accreted by those gaseous planets, including sub-Neptunes, within ∼1 au (e.g., Bean et al 2021;Izidoro et al 2022).…”
Section: Introductionmentioning
confidence: 95%